2007
DOI: 10.1021/ic700888w
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigation of β-Galactosidase-Activated MR Contrast Agents

Abstract: We report a mechanistic investigation of an isomeric series of β-galactosidase-activated magnetic resonance contrast agents. Our strategy focuses on the synthesis of macrocyclic caged-complexes that coordinatively saturate a chelated lanthanide. Enzyme cleavage of the complex results in an open coordination site available for water that creates a detectable MR contrast agent. The complexes consist of a DO3A Gd(III) chelator modified with a galactopyranose at the N-10 position of the macrocycle. We observed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 34 publications
2
63
0
Order By: Relevance
“…For instance, ligands such as 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (H 4 DOTA) and 1,4,7,10-tetraazacyclododecane-1,4,7-triacetic acid (H 3 DO3A) form lanthanide complexes of exceptionally high thermodynamic and kinetic stability. [15] Furthermore, the heptadentate ligand H 3 DO3A can be easily functionalized on the secondary amine nitrogen atom, a property that has been exploited to prepare a wide range of Ln 3+ -DO3A derivatives containing biologically, [16] chemically [17] or photochemically [18] active moieties.…”
Section: Wwweurjicorg Full Papermentioning
confidence: 99%
“…For instance, ligands such as 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (H 4 DOTA) and 1,4,7,10-tetraazacyclododecane-1,4,7-triacetic acid (H 3 DO3A) form lanthanide complexes of exceptionally high thermodynamic and kinetic stability. [15] Furthermore, the heptadentate ligand H 3 DO3A can be easily functionalized on the secondary amine nitrogen atom, a property that has been exploited to prepare a wide range of Ln 3+ -DO3A derivatives containing biologically, [16] chemically [17] or photochemically [18] active moieties.…”
Section: Wwweurjicorg Full Papermentioning
confidence: 99%
“…Further mechanistic investigations were reported which demonstrated that varying substitutions patterns on the linker between the galactopyranose and cyclen had a profound effect on the MR image produced. 138 Structural isomers of EGadMe 32-a and the mechanism for enzyme activation in both the presence and absence of carbonate was explored. It was determined that the position of the methyl group (32-a or 32-b) had a significant impact on the mechanism of water exclusion prior to enzymatic cleavage with the stereochemistry of the methyl group appearing to play no significant role.…”
Section: Probes Based On Lanthanide Relaxivitymentioning
confidence: 99%
“…This caged complex has all nine coordination sites of Gd(III) saturated, limiting access of water to the paramagnetic ion. Upon cleavage of the galactopyranose moiety from the chelate by β-gal, water access is restored resulting in an increase in relaxivity and signal enhancement on a T 1 -weighted image (Figure 3) [107, 108]. Enzymatic processing of the agent modulates the T 1, and in Xenopus laevis the detection of LacZ was shown in vivo [25].…”
Section: Optical and Mri Reporter Genes Based On Enzymatic Activitymentioning
confidence: 99%
“…Further modifications of this class of β-galactosidase activated probes have allowed for the determination of the mechanism that modulates this change in the coordination environment of the Gd(III) ion [108]. A series of isomers were synthesized with a methyl group substituted at the α or β position of the linker (α-EgadMe and β-EgadMe respectively).…”
Section: Optical and Mri Reporter Genes Based On Enzymatic Activitymentioning
confidence: 99%
See 1 more Smart Citation